2007
DOI: 10.1152/ajpheart.00910.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of collagen synthesis by inhibitory Smad7 in cardiac myofibroblasts

Abstract: Transforming growth factor-beta(1) (TGF-beta(1)) signal and downstream Smads play an important role in tissue fibrosis and matrix remodeling in various etiologies of heart failure. Inhibitory Smad7 (I-Smad7) is an inducible regulatory Smad protein that antagonizes TGF-beta(1) signal mediated via direct abrogation of R-Smad phosphorylation. The effect of ectopic I-Smad7 on net collagen production was investigated using hydroxyproline assay. Adenovirus-mediated I-Smad7 gene (at 100 multiplicity of infection) tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 66 publications
3
54
0
Order By: Relevance
“…Activation of resident cardiac fibroblasts into hypersynthetic/secretory myofibroblasts is now generally regarded as the seminal event in the upregulation and enhanced deposition of fibrillar collagens and ECM, which in acute phases assists in cardiac wound healing but in chronic phases ultimately culminates in cardiac dysfunction due to global stiffening of the noninfarcted myocardium remote to the infarct scar (8,34,40,42,43,45). Traditional TGF␤ 1 /Smad signaling has been described as a key regulator of the fibrotic response in the post-MI heart (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of resident cardiac fibroblasts into hypersynthetic/secretory myofibroblasts is now generally regarded as the seminal event in the upregulation and enhanced deposition of fibrillar collagens and ECM, which in acute phases assists in cardiac wound healing but in chronic phases ultimately culminates in cardiac dysfunction due to global stiffening of the noninfarcted myocardium remote to the infarct scar (8,34,40,42,43,45). Traditional TGF␤ 1 /Smad signaling has been described as a key regulator of the fibrotic response in the post-MI heart (44).…”
Section: Discussionmentioning
confidence: 99%
“…Of these factors, transforming growth factor ␤ 1 (TGF␤ 1 ) has been extensively described as a key regulator of the fibrotic response following tissue injury (5,13,15,36,37,43). TGF␤ 1 signals through a pair of membranebound serine/threonine kinase receptors that form heterodimers upon ligand binding (28,47).…”
Section: -Mediated Induction Of Scleraxis Via Inhibition Of P42/ P44mentioning
confidence: 99%
“…Multiple pathways can be activated by TGF-␤1. However, the SMAD 2/3 protein complex is recognized as a key mediator of TGF-␤1 profibrotic effects as the complex can translocate into the nucleus where it binds to gene promoter regions (37). SMAD 7 can inhibit the translocation of SMAD 2/3 by competing for the TGF-␤1 receptor binding site of SMAD 2/3 and also enhancing receptor degradation (24).…”
Section: Discussionmentioning
confidence: 99%
“…17 In vivo and in vitro studies revealed that overexpression of Smad7 inhibited collagen deposition induced by angiotensin II and TGFβ1 in cardiac fibroblasts and myofibroblasts. 18,19 In contrast, increased expression of β5 integrin subunit was associated with elevated collagen production in dermal fibroblasts. 20,21 Therefore, increased expression of ITGB5 and SMAD7, which was associated with BMI <30 in our study, may contribute to pro-and antifibrotic properties of BMSCs, respectively.…”
Section: Regulatory Molecules Implicated In Ecm Depositionmentioning
confidence: 94%